Natural and Social Sciences E-book Based on Inquiry Learning to Improve Higher Order Thinking Skills of Fourth Grade Elementary School Students - Kandi, Ni Nyoman Andi Sri; Wibawa, I Made Citra (Universitas Pendidikan Ganesha, 2024)
The low critical thinking ability of students is caused by a lack of student participation in learning and is dominated by teachers. Use of inappropriate media also causes this problem. Therefore, this research aims to analyze the effectiveness of E-book media based on Inquiry learning in improving the high-level thinking abilities of grade 4 students. The subjects used in this research were 17 grade students. This research uses the ADDIE model, which has the stages of Analysis, Design, Develop, Implementation, and Evaluation. The methods and instruments used are questionnaires and tests. The collected data was analyzed using qualitative descriptive and quantitative descriptive analysis techniques. The results show that the Science E-book based on Inquiry learning is valid, practical and effective for use in learning. Analysis of the effectiveness of e-books also shows a significant increase of 20.33% in students' HOTS abilities after using e-books. So it can be concluded that the Science E-book based on Inquiry learning is effective and has a positive influence in improving the HOTS abilities of class IV students at SDN 3 Kertha Mandala. The implications of this research show how important it is to create relevant science learning media to improve students' HOTS abilities.